The Effect of Current Ratio and Debt-to-Equity Ratio to Net Profit Margin in Food and Beverage Companies Listed in the Indonesia Sharia Stock Index for the Period 2014 - 2020 - Fathur Rochman (Prodi Manajemen Universitas Pamulang, 2022)
This study was conducted to find out how the Current Ratio and Debt to Equity Ratio affect the Net Profit Margin of food and beverage companies listed on the Indonesian sharia stock index for the period 2014 - 2020. The associative method is used in this study, with the population in the form of all food and beverage companies that contained in the Indonesian sharia stock index for the period 2014 - 2020. Through the purposive sampling method, a total sample of 10 food and beverage companies was obtained. Data analysis through multiple linear regression method. The test results show that partially Current Ratio affects Net Profit Margin significantly, Debt to Equity Ratio affects Net Profit Margin significantly. Simultaneously Current Ratio and Debt to Equity Ratio significantly affect Net Profit Margin